2007
DOI: 10.1248/jhs.53.282
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Epitopes on Human P-glycoprotein Recognized by Autoimmune Hepatitis Autoantibody as a Case Study

Abstract: Multiple drug resistant protein 1 (MDR1), P-glycoprotein, plays a role in the blood-brain barrier, preventing drug distribution into the brain, and in cancer chemotherapy. MDR1 is composed of two repeated fragments and there are six transmembrane domain (TMD) on the N-terminal of each repeat and a nucleotide-binding domain (NBD) on the C-terminal. We reported that sera from autoimmune hepatitis patients well reacted with MDR1 by enzyme-linked immuno-sorbent assay (ELISA) [Shinoda et al., (2004) Autoimmunity, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…We showed that the outer domain of human P-gp is recognized as an autoantigen against the autoantibody in autoimmune hepatitis [61,62]. We also reported an easy and sensitive method to measure P-gp activity [63].…”
Section: New Concept Of Structurementioning
confidence: 93%
“…We showed that the outer domain of human P-gp is recognized as an autoantigen against the autoantibody in autoimmune hepatitis [61,62]. We also reported an easy and sensitive method to measure P-gp activity [63].…”
Section: New Concept Of Structurementioning
confidence: 93%